Peran Guru Dalam Membantu Perkembangan Bahasa Anak Yang Sedang Mengalami Gangguan Berbicara (Spech Delay) - Malvin Regi Pramesta; Hendra Setiawan (Peneliti.net, 2023)
This study aims to describe the role of the teacher in helping children's language development. The teacher facilitates children by always listening to children when children talk, always responding when children speak, and always listening to ideas conveyed by children. Teachers use learning media such as audio-visual media (television), visual media (pictures), and audio media (listening to songs/recordings). This shows that the role of the teacher in helping the language development of children with speech disorders is successful.